Scientific landscape of oxidative stress in sarcopenia: from bibliometric analysis to hotspots review - Wang, Linjie; Guo, Dongliang; Huang, Yi; Long, Pan; Zhang, Xin; Bai, Ling; Liu, Jiancheng; Hu, Xiaomin; Pang, Rizhao; Gou, Xiang (Frontiers in Medicine, 2024)
Sarcopenia is a significant healthcare challenge in the aging population. Oxidative stress (OS) is acknowledged to play a pivotal role in the pathological progression of sarcopenia. Numerous studies have demonstrated that mitigating or eliminating OS can ameliorate the pathological manifestations associated with sarcopenia. However, current clinical antioxidant therapies often fall short of anticipated outcomes. This bibliometric analysis aims to delineate prevailing research trends, thematic emphases, focal points, and developmental trajectories within the domain of OS in sarcopenia, while also endeavoring to explore prospective anti-oxidative stress strategies for future clinical interventions. Relevant publications were retrieved from the Web of Science (WOS) Core Collection database for the period 2000-2024. Citespace was employed for retrieving and analyzing trends and emerging topics. In the field of OS in sarcopenia, the number of publications has significantly increased from 2000 to 2024. The United States and China are the primary contributors to global publication output. The most productive research institution is INRAE. The most prolific author is Holly Van Remmen from the United States, while the most frequently cited author is Cruz-Jentoft AJ from Spain. Experimental Gerontology is the journal with the highest volume of published articles, whereas the Journal of Gerontology Series A: Biological Sciences and Medical Sciences holds the record for the highest number of citations. The research keywords in this field can be categorized into eight domains: "Physiology and anatomy", "Physiological mechanisms", "Pathology associations", "Experimental studies", "Nutrition and metabolism", "Sports and physical activities", "Age" and "Oxidation and antioxidation". Moreover, recent years have seen the emergence of "TNFα", "insulin resistance", "mitochondrial autophagy", "signal pathways", and "mechanisms" as focal points in the realm of OS in sarcopenia, encompassing related fundamental research and clinical translation. Given the expectation that research on OS in sarcopenia will remain a prominent area of interest in the future, this article could serve as a valuable resource for scholars seeking to shape future studies through an understanding of influential scholarly contributions and key research findings.